Labor Market Issues in Belgium : An International Perspective - Moghadam, Reza. (Washington, D.C. : International Monetary Fund, 1993)
The characteristics of the Belgian labor market are examined using international comparisons in order to assess the government's recent labor market initiatives. The labor market in Belgium is found to suffer from a number of structural problems compared to other industrial countries: the non-employment rate is very high, there are large regional disparities in unemployment, female and youth unemployment are prevalent and there is an unusually pronounced incidence of long-term unemployment. The causes of these problems are investigated. The empirical results, using cross section data from 15 industrial countries, show that the generosity of long-term unemployment benefits helps to explain the prevalence of long-term unemployment. Unemployment compensation also appears to be paid to many who are not actively seeking work. The recent labor market initiatives in Belgium will help to ameliorate some of the underlying problems but they are unlikely to completely address the underlying structural problems.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet